BENEFITS OF VOLUMETRIC COMPRESSION OSCILLOMETRY FOR THE ASSESSMENT OF HEMODYNAMIC PARAMETERS IN PATIENTS WITH ARTERIAL HYPERTENSION - L. V. Shpak; E. S. Galoshina (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To compare the parameters of central and peripheral hemodynamics in healthy people and patients with Stage 1–3 arterial hypertension (AH).Material and methods. In total, 105 individuals were examined. The control group (CG) included 50 healthy people (25 women and 25 men; mean age 27,8±0,8 years) with optimal and normal levels of blood pressure (BP) (mean levels 118,5±1,6/71,82±1,2 mm Hg). The main group (MG) included 55 patients (41 women and 14 men; mean age 62,9±1,6 years) with systolo-diastolic AH: Stage 1 in 25 (mean BP levels 146,1±0,9/84,9±1,6 mm Hg), Stage 2 in 20 (164,4±1,8/95±2,1 mm Hg), and Stage 3 in 10 (189,6±10,6/92,6±6,3 mm Hg). The method of volumetric compression oscillometry (VCO) was used to assess a wide range of myocardial and hemodynamic parameters.Results. In AH patients, all AH phenotypes, vascular and cardiac parameters were increasing, with a simultaneous reduction in vascular wall distensibility, in parallel with the AH progression from Stage 1 to Stage 3. This indicated an increase in myocardial contractility, tone strain of arterial wall, and peripheral vascular resistance. From Stage 1 to Stage 3, the prevalence of hyper- and eukinetic cardiac hemodynamic types was decreasing, while the prevalence of mixed and hypokinetic types was increasing. The mixed hemodynamic type (a combination of hyper-, eu-, and particularly hypokinetic type characteristics) was considered as an incompletely developed disadaptive hypokinetic type.Conclusion. The VCO method is an effective, non-invasive way to simultaneously assess the status of multiple hemodynamic parameters in both healthy people and AH patients. A specific benefit of this method is the registration of lateral BP levels and identification of mixed (additional) hemodynamic type.